Hybrid Overlayer of Defective Ni-MOF and NiO Nanoparticles toward Efficient TiO2/CdS Type-II Heterojunction - Peng, Pai (Langmuir : the ACS journal of surfaces and colloids, 2024)
The severe photocorrosion of cadmium sulfide (CdS) restricts its practical application for solar hydrogen production. Although remarkable progress has been achieved with an overlayer strategy for isolating the CdS surface, the lifetime of CdS-based photoanodes is still far from the actual requirements. Herein, a hybrid overlayer of defective Ni-MOF and NiO nanoparticles has been developed through the chemical bath deposition method with postannealing. This hybrid overlayer of Ni-MOF-d is coated on the surface of the TiO2/CdS type-II heterojunction. The composite photoanode exhibits a photocurrent density of 4.41 mA cm-2 at 1.23 VRHE, which is 3.47- and 1.32-fold that of CdS and TiO2/CdS, respectively. The Ni-MOF-d overlayer gives rise to a negative shift of the onset potential by 59.51 mV. After a long-term stability test of 11 h, a photocurrent retention of 70% is observed, which is among the most robust CdS-based photoanodes. The kinetics studies reveal that the performance improvements can be attributed to the multiple functions of the Ni-MOF-d hybrid overlayer, including isolating the CdS surface from the electrolyte, cocatalyzing the electrode oxidation processes, passivating the surface defect states of CdS, and facilitating the charge injection from the photoanode to the electrolyte